Crop-management practices influence weed dynamics, yield and economics of soybean (Glycine max) - Meena, S.N.; Sharma, S.K.; Singh, Pratap; Jadon, Chaman K.; Jat, Mangi Lal; Meena, R.L (Indian Society of Agronomy, 2022)
A field experiment was conducted during 2018 and 2019 at Rajasthan College of Agriculture, Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan, to study the effect of crop-management practices on weed dynamics, yield and economics of soybean [Glycine max (L.) Merr.]. The experiment was laid out in randomized block design with 4 replications, comprising 5 treatments of different crop-management practices, viz. conservation organic, conservation chemical, conventional chemical, organic management + conventional tillage and package of practices. The results showed that, conservation chemical was found the most effective in controlling total weeds (5.5 m2 ) and reduction of dry-matter accumulation by weeds (24.8 kg/ha) as compared to the package of practices, conventional chemical, conservation organic and organic management + conventional tillage at 30 days after sowing (DAS). However, at 45 DAS, conservation organic was the most effective in controlling total weeds (5.9 m2 ) and reduction of dry-matter accumulation by weeds (35.9 kg/ha) as compared to organic management + conventional tillage, conservation chemical, package of practices and conventional chemical on pooled basis. Significantly higher seed (1,850 kg/ha), haulm (2,824 kg/ha), net returns (`48,913/ha) and benefit : cost ratio (3.2) of soybean were recorded under conservation chemical followed by package and practices and conventional chemical.